2010
DOI: 10.2165/11204930-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Long-Acting Injection

Abstract: Olanzapine pamoate (olanzapine long-acting injection [OLAI]; Zypadhera®; Zyprexa® Relprevv™) is the intramuscular depot formulation of the atypical antipsychotic olanzapine. In two pivotal, double-blind clinical trials of 8 or 24 weeks' duration, the efficacy of recommended dosages of OLAI injected every 2 or 4 weeks (without oral supplementation) was greater than that of placebo in improving symptoms in acutely ill patients with schizophrenia, and generally similar to that of continuing oral olanzapine in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Nevertheless, redness, pain, swelling, and nodule formation at the site of injection have been reported with both these compounds (3, 2326). The LAI formulation of olanzapine pamoate monohydrate (Zyprexa Relprevv®) has an incidence of injection site reactions of 8.4%, similar to what was reported with haloperidol (4, 27, 28) . Aripiprazole monohydrate (Abilify® Maintena™), recently approved by the U.S. Food and Drug Administration (FDA)-as an extended release formulation, has a reported injection site-related adverse events of 6.3%, with investigator evaluation noting injections site pain, redness, swelling, and induration in 4–26% of subjects in open label stabilization phase studies (38) , (29).…”
Section: Introductionsupporting
confidence: 61%
“…Nevertheless, redness, pain, swelling, and nodule formation at the site of injection have been reported with both these compounds (3, 2326). The LAI formulation of olanzapine pamoate monohydrate (Zyprexa Relprevv®) has an incidence of injection site reactions of 8.4%, similar to what was reported with haloperidol (4, 27, 28) . Aripiprazole monohydrate (Abilify® Maintena™), recently approved by the U.S. Food and Drug Administration (FDA)-as an extended release formulation, has a reported injection site-related adverse events of 6.3%, with investigator evaluation noting injections site pain, redness, swelling, and induration in 4–26% of subjects in open label stabilization phase studies (38) , (29).…”
Section: Introductionsupporting
confidence: 61%
“…OLZ selectively reduces the activity of dopaminergic mesolimbic (A10) neurons but not dopaminergic striatal (A9) neuron fire and, in animal studies, counteracts conditioned avoidance behavior (test of antipsychotic efficacy) at a dose that is not sufficient to induce catalepsy (test of motor side effect) (Chiodo and Bunney, 1983[25]; Stockton and Rasmussen, 1996[142]; Frampton, 2010[51]). More recently, preclinical studies have shown that OLZ efficacy on psychotic and cognitive symptoms of schizophrenia may be represented by its facilitating effect on N-methyl-D-aspartic acid, which can favor brain derived neurotrophic factor (BDNF) expression (Horacek et al, 2006[67]).…”
Section: Introductionmentioning
confidence: 99%
“…Olanzapine long-acting injection (LAI) has demonstrated efficacy in acutely ill patients [9] and has demonstrated similarity to oral olanzapine in terms of maintenance of effect and safety during longer-term treatment [10]; several recent reviews are available [11-13]. However, no direct comparisons of oral and LAI olanzapine have been done within the acute phase of treatment.…”
Section: Introductionmentioning
confidence: 99%